Autistic characteristics in youth with anorexia nervosa before and after treatment. (3rd July 2022) - Susanin, Annabel; Cooper, Marita; Makara, Amanda; Kuschner, Emily S.; Timko, C. Alix
Abstract: Objective: Cognitive characteristics common to autistic individuals are often seen in adults with anorexia nervosa (AN), raising the question of whether autistic people and people with AN may share an endophenotype. We need to examine autistic characteristics during the early stages of AN to accurately parse true symptom co‐occurrence from behavioural alterations due to prolonged illness. Methods: We conducted a post‐hoc analysis examining autistic characteristics in 59 youth with AN. Adolescents and parents participating in a randomised‐clinical trial for AN completed questionnaires probing autistic characteristics at baseline and treatment end. We categorised participants as above or below cut‐offs of clinical indicators of autism using the Autism Probability Index (API) and the Autism Spectrum Quotient‐10. Results: Rates of high autistic characteristics ranged between 0% and 36% depending on the instrument used and how the data was obtained (i.e., by informant report or self‐report). Paternal report of autistic characteristics differed across treatment completers versus non completers and maternal report indicated lower weight gain for those with elevated characteristics. Conclusions: Low rates of autism and fluctuations in autistic features during treatment underscore the importance of longitudinal examinations of autistic characteristics in adolescents with AN. Future studies need to replicate findings in a larger adolescent sample. Trial registration : ClinicalTrails.gov Identifier NCT03928028. Key points: Rates of autism characteristics in youth with anorexia nervosa depended on instrument used and informant. No association between autism characteristics and demographic, clinical, or treatment outcomes. Longitudinal examinations of autism characteristics in anorexia nervosa are needed.